Sistem Penegakan Hukum Pidana terhadap Pekerja Seks Komersial di Kota Palopo - Dian Eka Kusuma Wardani; Salim; Sutriyono (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to assess the implementation of criminal law against commercial sex workers in Palopo City. The main focus of this study is: (1) analyzing the implementation of law enforcement against commercial sex workers in the city, and (2) identifying the challenges faced and government efforts in overcoming these problems. This study uses a qualitative approach with an empirical legal basis. Data were collected through observation, interviews, and documentation studies, with the aim of obtaining relevant information directly from the field. This study reveals that law enforcement against commercial sex workers (CSWs) in Palopo City involves a number of agencies. The Palopo City Police carry out law enforcement through Operation Bina Kusuma, which includes supervision at lodgings and boarding houses, as well as various activities such as counseling, socialization, warnings, and discipline against CSWs. The Palopo City Social Service also plays a role by providing counseling, coaching, and assistance, including visiting the homes of CSWs and asking them to sign a statement. Meanwhile, Satpol PP of Palopo City prioritizes preventive measures and non-legal approaches in law enforcement. Problems related to sex workers in Palopo City are regulated in Palopo City Regional Regulation Number 10 of 2014 concerning the Implementation of Public Order and Security, especially in Article 40, which prohibits immoral behavior, including becoming sex workers, and urges other parties not to persuade or force individuals to engage in such work. However, law enforcement is hampered by the absence of more specific laws regarding sex workers and the absence of rehabilitation facilities in the city. Some proposed solutions include increasing community participation through socialization, creating more specific regional regulations regarding sex workers, a more humanitarian approach, and providing rehabilitation facilities.